Florence, Berlin and beyond : late nineteenth-century art markets and their social networks - Catterson, Lynn (Studies in the history of collecting & art markets., 2020)
"Recent and increasing interest in art market studies-the dealers, mediators, advisors, taste makers, artists, etc.-indicate that the transaction of art and decorative art is anything but linear. Taking as its point of departure two of the most active agents of the late nineteenth century, Wilhelm von Bode and Stefano Bardini, the essays in this volume also look beyond, to other art market individuals and their vast and frequently interconnected, social and professional networks. Newly told history taken from rich business, epistolary and photographic archives, these essays examine the art market, within a broader and more complex context. In doing so, they offer new areas of inquiry for mapping of works of art as they were exchanged over time and place"--